The Effect of Experience Quality on Customer Loyalty With Moderation Of Currency And The Role Of Conversation and Co-Creation on Vod Viu Customers In Bekasi District - Salsabilla, Meisya; Bintarti, Surya; Kurniawan, Ergo Nurpatria; Tanjung, Agustini (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine the relationship between Conversation and Co-Creation on Customer Loyalty through the mediation of Experience Quality moderated by Currency. This research uses quantitative methods. Sampling in this study used the Non Probability Sampling method with Purposive technique. The population used in this study is people in Bekasi Regency, with a sample obtained of 114 customer respondents who subscribe to Viu VoD services. This study tests correlation and regression with the help of the SmartPLS 3.2.9 program which is used to test validity and reliability. The results showed that Conversation has a significant positive role on customer Experience Quality. Co-creation has a significant positive effect on customer Experience Quality. Conversation with moderation Currency has a negative role on customer Experience Quality. Co-creation with Currency moderation has a significant positive effect on the level of customer Experience Quality. Customer Experience Quality has a significant positive role on Customer Loyalty. Conversation through the mediation of Experience Quality has a negative influence on Customer Loyalty. Co-creation through the mediation of Experience Quality has a significant positive effect on Customer Loyalty.